Speedy derivative-corrective mass spring algorithm for adaptive impedance matching networks - Wong, Yan Chiew; Arslan, Tughrul S.; Erdogan, Ahmet T.; Haridas, Nakul; El-Rayis, Ahmed O. (2012)
Adaptive impedance matching algorithms are used to preserve the link quality of mobile phones, under fluctuating user conditions. It is highly desirable to reduce the search time for minimising the risk of data loss during the impedance tuning process. Presented is a novel technique to reduce the search time by more than an order of magnitude by exploiting the relationships among the mass spring's coefficient values derived from the matching network parameters, thereby significantly reducing the convergence time of the algorithm.